2012
DOI: 10.4236/msa.2012.34034
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Hardness Distribution of High Pressure Torsion Processed IF Steel Disks

Abstract: The inhomogeneous hardness distribution of high pressure torsion (HPT) processed IF steel disks along different directions is investigated. The results indicated that there exists inhomogeneous distribution in HPT processed IF steel disks, giving lower hardness in the center and higher hardness in the edge regions. However, on the axisymmetrical section testing plane of the disks’ thickness direction, there is a soft zone near the surface of disks. Further results from radius testing plane of different depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Vorhauer and Pippan (2004) and Pippan et al (2008) among others reported that the microhardness varies significantly along the radius of disks processed by HPT at the early stages of deformation but that the hardness becomes homogeneous with a high level of deformation. Basically, the same results were found in various other investigations of simple metals [e.g., (Valiev et al, 2010;Song et al, 2012;Borodachenkova et al, 2017;Rijal et al, 2020)]; unfortunately, no distribution of density is given in these publications. For three CP + HPT samples static hardness was measured along the radius of the disk from the innermost point to the rim; results are shown in Figure 7.…”
Section: Hardnesssupporting
confidence: 75%
“…Vorhauer and Pippan (2004) and Pippan et al (2008) among others reported that the microhardness varies significantly along the radius of disks processed by HPT at the early stages of deformation but that the hardness becomes homogeneous with a high level of deformation. Basically, the same results were found in various other investigations of simple metals [e.g., (Valiev et al, 2010;Song et al, 2012;Borodachenkova et al, 2017;Rijal et al, 2020)]; unfortunately, no distribution of density is given in these publications. For three CP + HPT samples static hardness was measured along the radius of the disk from the innermost point to the rim; results are shown in Figure 7.…”
Section: Hardnesssupporting
confidence: 75%
“…An important point should be paid attention to that the lower hardness areas are only in both the outedge and center near the disks' surface. However, a high value of hardness exists near the central position on the thickness direction named hardness hill from literatures [35,36]. In order to clearly display this inhomogeneity, the edge microstructure on the different testing plane (transversal and radial) of compressed disk under 2.5 GPa pressure is shown in Figure 9.…”
Section: Severe Plastic Deformation Techniquesmentioning
confidence: 97%
“…Presently, there are at least three aspects existing controversy in HPT field: Firstly, HPT processing consists of two stages (compression stage and torsion stage under high pressure stages, as shown in Figure 1). Most of the reports published focused on the last stage [32,[36][37][38], but there are few researchers directly on the role of compressive processing stage [39,40]; second, because the developed strain at the center of the disk is theoretically zero and linearly increases with the distance from the center according to the characteristics of torsional strain, it is reasonable to anticipate that the microstructures produced by the HPT process will be extremely inhomogeneous. However, recently, papers demonstrated that the microstructure is reasonably homogeneous across the disks when the torsional straining continues; at last, although a lot of studies have been done on HPT [32,[36][37][38][39][40], most of them are for microstructure and its Ultrafine-Grained Materials Fabrication with High Pressure Torsion and Simulation of Plastic... http://dx.doi.org/10.5772/intechopen.68360 characterization or for processing.…”
Section: Severe Plastic Deformation Techniquesmentioning
confidence: 99%
“…For the HPT processing, the sample is usually used in disk shape with the thickness less than 1 mm but a few studies were attempted on thicker samples [20][21][22][23][24][25][26][27]. By changing the ratio of the thickness to the diameter of the disk, Hohenwarter et al [22] examined the effect of the thickness on the microstructural homogeneity and reported that there was a thickness limitation for achieving homogeneous microstructure throughout the thickness direction.…”
Section: Introductionmentioning
confidence: 98%